Saraswati - "Valdiya, K S" (New Delhi, 2002)
This book is about the River Saraswati that vanished more than 2000 years ago. Written in simple language shorn of technical jargon, it explores the existence of a mighty, snow-fed river, traces its course from the foothills of the Himalayas to the shores of the Arabian Sea and outlines the history of human settlements along this river. It finally highlights the geological events that overtook the land leading to the disappearance of the river that was once the lifeline of the people that inhabited its floodplain. It is lavishly illustrated in both colour and black and white.
Keywords: Rivers